PENERAPAN METODE PEMBELAJARAN THINK PAIR SHARE UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI KEBUGARAN JASMANI DI SMK KANSAI PEKANBARU - Rahmadani, Rahmadani; Sulastio, Agus; S, Wedi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstract: Physical education is a learning process through useful activities toimprove a person's quality and train psychomotor skills to achieve the desired goals. In physical education there are several aspects, one of which is physical fitness. According to Wirnantika (2017) in Cristiana (2020), physical fitness activities can be carried out every day without experiencing significant fatigue, so that you still have the energy to carry out other activities. Cooperative Learning is a learning model developed to achieve learning outcomes in the form of academic achievement, tolerance, acceptance of diversity, and skill development." This means that Cooperative learning is a learning used by teachers so that students achieve certain results. Apart from that, through the application of the cooperative learning model, students will learn how to respect the opinions of their friends, accept diversity and develop skills in expressing their opinions. The Think Pair Share method is called a pair learning method. This method was first developed by Frank Lyman from the University of Maryland as a structure for mutual cooperation learning activities. This model provides opportunities for students to work alone and collaborate with others. Think Pair Share has procedures explicitly implemented to give students more time to think, answer, and help each other. Think Pair Share is a simple learning method with big benefits. Think Pair Share can improve students' ability to understand and remember information, students also learn from other students, and share their ideas with each other in the group work process. Think Pair Share also increases self-confidence, students are given the opportunity to participate in class and present the results of their group discussions in front of the class. Based on the description of the background, the author concludes that the ThinkPair Share learning method can create active, effective and non-monotonous learningduring the learning process, thereby making students not feel bored during learning.Key Words: Learning, Fitness